2014
DOI: 10.1111/micc.12138
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of H1 and H2 Receptors and Soluble Guanylate Cyclase in Histamine‐Induced Relaxation of Rat Mesenteric Collecting Lymphatics

Abstract: Objective This study investigated the roles of the H1 and H2 histamine receptors, nitric oxide (NO) synthase, and soluble guanylate (sGC) cyclase in histamine-induced modulation of rat mesenteric collecting lymphatic pumping. Methods Isolated rat mesenteric collecting lymphatics were treated with 1–100 μM histamine. Histamine receptors were blocked with either the H1 antagonist mepyramine or the H2 antagonist cimetidine. The role of NO/sGC signaling was tested using the arginine analog L-NAME, the sGC inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…Cromolyn has previously been reported to block mast cell activation and to inhibit histamine secretion from rodent peritoneal mast cells [9, 122, 123]; (4) treated with compound 48/80 plus a mixture of histamine receptor (HR) blockers added to PSS in order to block all 4 types of HRs and to prevent the potential effect of histamine on NF-κB activation. We added a mixture of the following HR blockers: pyrilamine maleate (1 μM [30]) (Sigma Aldrich, St. Louis, MO, USA, catalog # P5514); cimetidine (100 μM [124]) (Sigma Aldrich, St. Louis, MO, USA, catalog # C4522) and thioperamide maleate (1 μM [125]) (Sigma Aldrich, St. Louis, MO, USA, catalog # T123). The mesenteric segments were treated as follows: (1) sham control for 5 hours; (2) sham treatment for 2 hours followed by compound 48/80 for another 3 hours, to induce activation of mast cells; (3) pre-treated with cromolyn sodium for 2 hours, in order to block mast cell activation and to inhibit histamine secretion from rodent peritoneal mast cells, then treated with compound 48/80 plus cromolyn for another 3 hours; (4) pre-treated with the mixture of HR blockers for 2 hours, in order to block all 4 types of HRs, then treated with compound 48/80 plus HR blockers for another 3 hours at 38ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Cromolyn has previously been reported to block mast cell activation and to inhibit histamine secretion from rodent peritoneal mast cells [9, 122, 123]; (4) treated with compound 48/80 plus a mixture of histamine receptor (HR) blockers added to PSS in order to block all 4 types of HRs and to prevent the potential effect of histamine on NF-κB activation. We added a mixture of the following HR blockers: pyrilamine maleate (1 μM [30]) (Sigma Aldrich, St. Louis, MO, USA, catalog # P5514); cimetidine (100 μM [124]) (Sigma Aldrich, St. Louis, MO, USA, catalog # C4522) and thioperamide maleate (1 μM [125]) (Sigma Aldrich, St. Louis, MO, USA, catalog # T123). The mesenteric segments were treated as follows: (1) sham control for 5 hours; (2) sham treatment for 2 hours followed by compound 48/80 for another 3 hours, to induce activation of mast cells; (3) pre-treated with cromolyn sodium for 2 hours, in order to block mast cell activation and to inhibit histamine secretion from rodent peritoneal mast cells, then treated with compound 48/80 plus cromolyn for another 3 hours; (4) pre-treated with the mixture of HR blockers for 2 hours, in order to block all 4 types of HRs, then treated with compound 48/80 plus HR blockers for another 3 hours at 38ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Lymphatic pumping is negatively regulated by histamine (87, 88) and nitric oxide (NO), which potently inhibits lymphatic muscle contractions (8991). In general, NO may be produced either by lymphatic endothelium through endothelial NO synthase (eNOS), or during inflammatory states by nearby immune cells through inducible NO synthase (iNOS) (90).…”
Section: Structure and Properties Of The Lymphatic Systemmentioning
confidence: 99%
“…Several studies have identified that the mechanism for flow-mediated modulation of the lymphatic contractile cycle requires endothelial production of NO (Gashev et al, 2002; Mizuno et al, 1998; Shirasawa et al, 2000; von der Weid et al, 1996; von der Weid et al, 2001). Presumably the action of NO is activation of soluble guanylate cyclase, accelerated production of cGMP, and activation protein kinase G (Gasheva et al, 2013; Kurtz et al, 2014a). Interestingly, in aged rats (22 months old), shear stress-induced relaxation of lymphatic smooth muscle is only partially inhibited by blockade of NO synthase, unlike the 9-month old controls (Nagai et al, 2011).…”
Section: Fluid Shear Stress From Lymph Flow and Collecting Lymphatic mentioning
confidence: 99%
“…The permeability coefficients for albumin determined from single-perfused rat mesenteric lymphatic vessels lie within the same range as those for postcapillary venules (Scallan and Huxley, 2010). Like postcapillary venules, collecting lymphatics have continuous VE-cadherin labeling at their endothelial intercellular junctions (Baluk et al, 2007; Kurtz et al, 2014a; Wong et al, 1999). This pattern is also seen in cultured lymphatic endothelial cells, grown either as monolayers or in tubes (Breslin et al, 2007a; Price et al, 2008).…”
Section: Permeability Of Collecting Lymphaticsmentioning
confidence: 99%